Dietary Practice and Associated Factors Among Pregnant Women at Public Health Institution in Mizan-Aman Town, Southwest Ethiopia - Abel Girma Tilahun (SAGE Publishing, 2021)
Background: A poor dietary intake of key macronutrients and micronutrients adversely affects pregnancy outcomes and neonatal health. The occurrence of dietary inadequacy during pregnancy is higher compared to any other stage of the life cycle. Therefore, this study aimed to assess dietary practice and associated factors among pregnant women. Methods: A facility-based cross-sectional study design was conducted among 378 pregnant women from March to May 2021 at the public health institution of Mizan-Aman town, southwest Ethiopia. A systematic random sampling technique was used to reach the study participants. The short food-frequency questionnaires and nutrition-behaviors checklist measurement were used to assess the dietary practice. Nine questions were applied to assess the dietary attitudes of the respondents. After the summation of the score, the respondent was categorized as favorable attitude if their score was > the median and unfavorable attitude if their score was ⩽ to the median of the score. The data were entered into Epi Data 3.1 and exported to Statistical Package for Social Science (SPSS) version 21 software for analysis. Variables of P -value <.25 during bivariate logistic regression analysis were considered for multivariate analysis. Finally variables with an adjusted odds ratio of P -value <.05 along with a 95% Confidence interval (CI) were declared statistically significant. Results: The overall magnitude of good dietary practice among pregnant women was 25.1% (95% CI: 20.9, 29.71%). In multivariate logistic regression analysis, the variables having television/radio (AOR = 4.2, 95% CI: 1.8, 10.2), household food security (AOR = 3.1, 95% CI: 1.0, 9.9), good dietary knowledge(AOR = 4.1, 95% CI: 1.98, 8.6), favorable dietary attitude (AOR = 4.34, 95% CI: 1.2, 8.7), monthly income of 1000 to 2000 Ethiopian birr (AOR = 3.7, 95% CI: 1.3,11.2) and >2000 Ethiopian birr (AOR = 7.0;95% CI: 3.3,15.4) were significantly associated with good dietary practice. Conclusion: The dietary practice among pregnant women was very low. The factors like having television/radio, good dietary knowledge, household food security, favorable dietary attitude, and monthly income of 1000 to 200 and greater than 2000 Ethiopian birr were significantly associated with the good dietary practice of pregnant women.